1990
DOI: 10.1093/infdis/162.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B in a Highly Active Prostitute Population: Evidence for a Low Risk of Chronic Antigenemia

Abstract: The epidemiology of hepatitis B in female prostitutes was studied in a cross-sectional survey of 467 prostitutes and 510 control prenatal clinic patients from Lima and Iquitos, Peru. Prostitutes reported a mean of 8.8 +/- 6.7 years of active prostitution and a mean of 205 +/- 137 sexual contacts in the month prior to the study. Hepatitis B surface antigen (HBsAg) was found in comparable percentages of prostitutes (1.7%) and controls (0.8%; P = .305). In contrast, seropositivity for both antigen and antibody ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
2
16
1
1
Order By: Relevance
“…[52][53][54][55][56] Sex workers are also at higher risk. 57,58 . Other routes are: vertical (infected mother to infant), parenteral (unscreened blood and blood products, injecting drug users sharing needles, syringes and other 'works', occupational needlestick injuries, nonsterile acupuncture and tattoo needles).…”
Section: Transmissionmentioning
confidence: 99%
“…[52][53][54][55][56] Sex workers are also at higher risk. 57,58 . Other routes are: vertical (infected mother to infant), parenteral (unscreened blood and blood products, injecting drug users sharing needles, syringes and other 'works', occupational needlestick injuries, nonsterile acupuncture and tattoo needles).…”
Section: Transmissionmentioning
confidence: 99%
“…22 23 However, hepatitis B virus is also eYciently transmitted sexually during heterosexual and male homosexual contact. [24][25][26][27] HETEROSEXUAL TRANSMISSION Several studies have shown that heterosexual transmission is important in female sex workers [28][29][30] and their customers 31 in countries where the prevalence of HBV carriers is high. In one study of Peruvian female prostitutes, 59.8% had evidence of past hepatitis B infection and over the next 3 years the non-immune prostitutes became infected at 4.7% per year, excluding parenteral transmission.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…28 Evidence of past or current hepatitis B infection was four to six times higher in non-drug using prostitutes than in controls in this and other studies and correlated with number of sexual contacts and sexually transmitted diseases. [28][29][30] Outside of prostitution, heterosexual transmission is still important as shown by the 40% transmission rates to non-immune spouses of patients with acute or chronic hepatitis B. 24 32 There are no clear data on the mechanism of transmission but it is assumed to be unprotected vaginal intercourse.…”
Section: Hepatitis Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuncel ve arkadaşları (33) ise, hayat kadınlarında bu oranlan % 8.9 ve % 50.5 olarak bildirmektedir. Hayat kadmlan HBV için önemli risk grubundadır (1,16,19,21). HBsAg pozitif annelerden transplasenter, özellikle perinatal bulaşlar olmakta ve kordon kanında % 0-80 HBsAg pozitifliği bildirilmektedir (5,26,32,33).…”
unclassified